Expression of CYP3A in chronic ethanol-fed mice is mediated by endogenous pregnane X receptor ligands formed by enhanced cholesterol metabolism - Je, Young-Tae; Sim, Woo-Cheol; Kim, Dong-Gwang; Jung, Byung-Hwa; Shin, Ho-Sang; Lee, Byung-Hoon (SPRINGER HEIDELBERG, 2015)
Pregnane X receptor (PXR) is a nuclear receptor that plays a key regulatory role in xenobiotic metabolism in a ligand-dependent manner. Recently, ethanol was reported to be either an inducer or inhibitor of Cytochrome P450 (CYP) 3A expression. According to our recent microarray data, chronic ethanol upregulates the expression of the genes associated with oxidative phase I drug metabolism, phase II conjugation reaction and phase III xenobiotic transport, most of which are known to be regulated by PXR. In this study, we investigated the effects of chronic ethanol on the expression and activity of CYP3A11 in mice and the role of PXR. Ethanol was administrated to male ICR mice by feeding a standard Lieber-DeCarli diet containing 36 % ethanol for 4 weeks. Ethanol significantly increased hepatic mRNA expression of Pxr and Cyp3a11. Treatment of mice with ethanol increased nuclear translocation of PXR. Consistent with the increase in nuclear PXR, ethanol significantly increased the binding of PXR to the Cyp3a11 promoter. Hepatic cholesterol level and bile acid synthesis are increased by ethanol treatment. The level of some cholesterol metabolites, such as 5 beta-cholestane-3 alpha,7 alpha,12 alpha-triol, 7 alpha-hydroxy-4-cholestene-3-one and lithocholic acid, that have been identified as potent PXR agonists are increased in the livers of ethanol-treated mice. In summary, chronic ethanol upregulates the expression of Pxr and Cyp3a11 mRNAs and proteins in mice by PXR activation mediated by enhanced cholesterol metabolism and bile acid synthesis. Our data provide some critical information needed to understand the molecular mechanisms of ethanol-induced CYP3A expression.
Keywords: CONSTITUTIVE ANDROSTANE RECEPTOR; MICROSOMAL-ENZYME INDUCERS; HUMAN LIVER-MICROSOMES; NUCLEAR RECEPTORS; DRUG-METABOLISM; MOUSE-LIVER; CYTOCHROME-P-450 3A4; LITHOCHOLIC ACID; GENE-EXPRESSION; PXR